Microcomposites from Recycled Polypropylene Plastic with Reinforcement Fiber of Oil Palm Empty Fruit Bunches - Zulnazri; Rozanna Dewi (Proceedings of International Conference on Multidisciplinary Engineering (ICOMDEN), 2018)
This study describes the processing of thermoplastic polypropylene from used plastic packaging with filler of palm oilbunches as a composite. Polypropylene material is crushed and melted using xylene solvent and then mixedhomogeneously with micrometer-sized filler, then presses using a hot press at a temperature of 165oC. Methods ofphysical and chemical modification of fibers with polypropylene matrix and the addition of several additives werecarried out to improve compatibility, mechanical properties, morphology, electrical properties and biodegradability ofcomposites. Analysis of mechanical properties obtained tensile strength of 13.053 MPa, elastic modulus of 455.252MPa, impact of 3019.1 J/m2. Infra reed (FT-IR) analysis shows that the -OH functional group of fibers places a positionadjacent to the polypropylene functional group. Surface structure analysis (SEM) showed that the fiber bond strengthbetween the matrix and the analysis of thermal properties showed a high melting temperature of 488.33oC